Crystal structures and luminescent properties of terbium(III) carboxylates - Barja, Beatriz Carmen (2003)
Single crystals of three terbium(III) carboxylates of formulae [Tb2(CH3COO)6(H2O)4]/4H2O (1), [Tb2(CF3COO)6(H2O)6] (2) and [Tb(Hoda)3]/H2oda/H2O (3) (H2oda=2,2-oxydiacetic acid) were obtained and their structures determined by X-ray crystallography. Compounds 1 and 2 are dimeric, in the former the terbium atoms are bound by two tridentate carboxylates in the m2- bridging mode, whereas in the latter the bridging is fourfold with all carboxylates in the syn /syn coordination mode. Compound 3 is mononuclear containing three tridentate Hoda anions, and consecutive units are linked by a network of H-bonds involving the interstitial molecules. The luminescence spectra of the carboxylates were analyzed in the solid state and in aqueous solution. Comparison of the emission lifetimes in H2O and D2O allowed the determination of the average value for q, the number of coordinated water molecules, being 9.2 for 1 and 2 and 3.6 for 3, respectively. The quenching effect of Cu(II) on the luminescence of the terbium(III) carboxylates was evaluated through the emission decay constants. From the addition of Cu(II) to an aqueous solution of 3, single crystals of polymeric [{Cu3Tb2(oda)6(H2O)6}/12H2O]n (4) were isolated with completely quenched luminescence. Compound 4 exhibits an overall antiferromagnetic interaction.